Assistance to the Majelis Taklim Based on Religious Moderation as an Effort to Form Adaptive Behavior of Minority Muslims with Local Culture in the Tengger Tribal Region - Marzuki, Ahmad; Kirom, Askhabul; Yusuf, Achmad (Jurnal Soeropati, 2024)
The existence of the taklim assembly has an important role in the socialization and enculturation process to enable Muslims to survive in a society that is predominantly Hindu. The role of the taklim assembly is expected to be able to present religious material that is able to form a moderate way of religion for its congregation, especially in responding to local culture in the Tengger tribe area. The focus of this service is first, local cultural study workshops and strengthening religious moderation. Second, strengthening Religious Moderation, through the development of religious material that will be presented in taklim assembly activities by the Muallim to the congregation. Based on these two focuses, service uses the service learning method through three stages; preparation, planning and implementation. From the results of the mentoring, the following are the results; 1) study of local Karo culture, entas-entas, barikan, kasodo, walagara, liliwet, santi, sodoran, and unan-unan. Local culture contains moral messages that can be used as material to strengthen religious moderation. 2) development of moral religious material that emphasizes the social dimension. Religious material contains messages about building relationships between humans and humans and humans and nature.